High-sensitivity bending sensor based on ionic polymer gel

By adopting a dual-network structure ion polymer gel and multi-layer electrode structure in the bending sensor, the existing sensor has low sensitivity and inability to identify the bending direction, and the functions of high sensitivity and multi-degree of freedom bending detection are achieved.

CN119573542AActive Publication Date: 2025-03-07SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311143405.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

Existing bending sensors have problems with low sensitivity and inability to distinguish bending direction and angle, and it is difficult to meet the needs of high sensitivity and multi-degree of freedom bending detection.

Method used

Using a highly sensitive bending sensor based on ion polymer gel, multi-degree of freedom bending detection and bending direction recognition is achieved through the dual-network structure of the ion gel center sensitive layer and the pair-attached electrode layer.

Benefits of technology

It achieves high bending response sensitivity and wide response range, can accurately identify bending direction and amplitude, and improves the sensitivity and stability of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119573542A_ABST
    Figure CN119573542A_ABST
Patent Text Reader

Abstract

The invention discloses a high-sensitivity bending sensor based on ionic polymer gel, and belongs to the technical field of flexible sensors. The high-sensitivity bending sensor based on the ionic polymer gel comprises an ionic gel center sensitive layer with a double-network structure and electrode layers attached to the surface of the ionic gel center sensitive layer in pairs, and the number of pairs of electrodes is larger than or equal to 1; preferably, the number of pairs of the electrodes is greater than or equal to 2; wherein the ionic gel center sensitive layer forms a double-network structure with intertwined molecular chains through cross-linking polymerization of a monomer of a zwitterionic polymer and a monomer of a flexible polymer. The device shows a multi-degree-of-freedom bending characteristic, has high bending response sensitivity and a wide response range, can identify the bending direction and amplitude, and has a wide application prospect in the field of man-machine interaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible sensors, and in particular relates to a highly sensitive bending sensor based on ionic polymer gel. Background Art

[0002] With the development of artificial intelligence, wearable electronic devices have shown great market prospects and are widely used in human motion monitoring, biomedicine, virtual reality and military fields. As the core component of flexible wearable electronic devices, they are light, portable and well conformal to the human body, which has attracted people's attention. Flexible bending sensors are flexible electronic devices that can convert the bending changes they endure into electrical signal outputs that are easy to collect and transmit, thereby accurately recording the bending deformation of the monitored object in real time. They have broad application prospects in the field of human-computer interaction.

[0003] The resistive, capacitive and piezoelectric bending sensors developed in the early stage can detect bending deformation, but they have problems such as low sensitivity and inability to distinguish bending direction and angle. Some researchers have prepared a resistive bending sensor by designing a reverse pyramid structure, which suppresses microcracks in a specified area under bending, helping the sensor to detect a wide range of bending strains, but the sensor cannot distinguish the bending direction (Reference 1). In order to enable the sensor to respond to bending in different directions, some researchers have proposed a resistive sensor with a gradient structural dispersion feature in polyurethane in which the active material is realized by gravity-driven self-assembly. The active material is tannic acid-modified MXene nanosheets. The asymmetry of the film gives it a response to directional bending, but the sensor has the disadvantage of low sensitivity (Reference 2).

[0004] Therefore, it is of great significance to develop a bending sensor with high sensitivity and the ability to recognize bending direction and angle.

[0005] Prior art literature:

[0006] Literature 1: Lee DH, Yang JC, Sim JY, et al. Bending Sensor Based on Controlled Microcracking Regions for Application toward Wearable Electronics and Robotics[J]. ACS applied materials&interfaces, 2022, 14(27): 31312-31320.

[0007] Document 2: Bai J, Gu W, Bai Y, et al. Multifunctional Flexible Sensor Based on PU-TA@MXene Janus Architecture for Selective Direction Recognition[J]. Advanced Materials 2023, 2302847. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a highly sensitive bending sensor based on ionic polymer gel. The device of the present invention exhibits multi-degree-of-freedom bending characteristics, has high bending response sensitivity and a wide response range, can identify bending direction and amplitude, and has broad application prospects in the field of human-computer interaction. To achieve the above purpose, the present invention adopts the following technical solutions:

[0009] In the first aspect, the present invention provides a highly sensitive bending sensor based on ionic polymer gel. The highly sensitive bending sensor based on ionic polymer gel comprises an ionic gel central sensitive layer having a double network structure and an electrode layer attached in pairs to the surface of the ionic gel central sensitive layer, wherein the number of pairs of electrodes is ≥1; preferably, the number of pairs of electrodes is ≥2; wherein the ionic gel central sensitive layer is cross-linked and polymerized by monomers of zwitterionic polymers and monomers of flexible polymers to form a double network structure in which molecular chains are intertwined with each other. When the number of electrode pairs is 1, the bending direction and bending amplitude detection on one degree of freedom can be realized. When the number of electrode pairs is greater than or equal to 2, multi-degree-of-freedom bending detection can be realized.

[0010] Preferably, the electrode layers are attached in pairs to the upper surface and the lower surface of the strip-shaped ion gel central sensitive layer to form a sandwich structure sensor that realizes one degree of freedom direction recognition.

[0011] Preferably, the electrode layers are attached in pairs to the four side walls of the strip-shaped ion gel central sensitive layer to form a long strip structure sensor that realizes two-degree-of-freedom direction recognition.

[0012] Preferably, the electrode layer is rectangular or serpentine-shaped by topological optimization; preferably, the electrode layer formed into a serpentine shape by topological optimization is attached in pairs to the four side walls of the strip-shaped ion gel central sensitive layer to form a long strip structure sensor that realizes bending recognition in two degrees of freedom directions.

[0013] Preferably, the double network structure comprises an elastic polymer skeleton formed by polymerization of monomers of a flexible polymer and a polyzwitterionic channel formed by a zwitterionic polymer; preferably, the monomer of the zwitterionic polymer is methacrylic acid sulfobetaine, and the monomer of the flexible polymer is acrylamide.

[0014] Preferably, the ion precursor solution of the central sensitive layer of the ion gel includes a free ion source and a solvent in addition to the monomers of the zwitterionic polymer and the monomers of the flexible polymer; wherein the anions and cations provided by the free ion source can move freely in the polyzwitterionic channel; preferably, the cation size of the free ion source is smaller than the anion. It is preferable that the size of the anion and the cation have a certain difference. The cation has a smaller radius and a faster migration speed, while the anion has a larger radius and a slower migration speed than the cation. Therefore, the greater the size difference between the anion and the cation, the greater the potential difference can be formed on both sides of the electrode, thereby improving the sensitivity of the device. The greater the size difference between the anion and the cation of the free ion source in the central sensitive layer of the ion gel, the greater the difference in migration rate during bending strain, the greater the potential difference formed, and the higher the response sensitivity of the sensor device. More preferably, the size difference between the anion and the cation of the free ion source is between 0.1-0.8nm.

[0015] Preferably, the free ion source is selected from one or more of zinc trifluoromethylsulfonyl imide, lithium trifluoromethylsulfonyl imide, and lithium chloride; the solvent is selected from at least one of water, an organic solvent, and a deep eutectic solvent, preferably water.

[0016] Preferably, the electrode layer includes a flexible substrate and a conductive material coated on the surface of the flexible substrate; the conductive material is selected from one or more of a specific microstructured metal film, metal particles, carbon nanotubes, metal nanowires, graphene, MXene, and a conductive polymer; preferably, the conductive material is deposited on the surface of the flexible substrate to obtain the electrode layer. The electrode layer has high conductivity, high flexibility, ductility, and conductivity stability under bending strain. High conductivity is conducive to the rapid transmission of electrical signals. Excellent flexibility is conducive to the common fit between the electrode and the ionic polymer layer, and improves the stability of interfacial charge transfer. A certain degree of ductility is required to match the deformation caused when the device is bent.

[0017] Preferably, the highly sensitive bending sensor based on ionic polymer gel senses bending through the potential difference formed by the asymmetric movement of anions and cations in the free ion source caused by bending.

[0018] Preferably, the highly sensitive bending sensor based on ion polymer gel further comprises an encapsulation layer covering the sensor surface; preferably, the material of the encapsulation layer is selected from polyethylene terephthalate, polyimide, polydimethylsiloxane, polymethyl methacrylate or silicone rubber. The encapsulation layer has good modulus adaptation with the ion gel central sensitive layer and the electrode layer, can achieve good bending deformation, and has a protective effect and a solvent barrier effect, can effectively prevent the solvent in the ion gel central sensitive layer from volatilizing, improve the stability of the ion polymer gel material, and increase the service life of the sensor.

[0019] In a second aspect, the present invention provides a highly sensitive bending sensor based on an ionic polymer gel as described in any of the above items, and the preparation method comprises: molding and curing the ion precursor solution of the ionic gel central sensitive layer to obtain the ionic gel central sensitive layer; attaching electrode layers in pairs to the surface of the ionic gel central sensitive layer to obtain the highly sensitive bending sensor based on the ionic polymer gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a diagram showing the sensing mechanism of the highly sensitive bending sensor based on ionic polymer gel of the present invention.

[0021] Figure 2 Scanning electron microscope images of single-network PAM hydrogel and double-network P(SBMA-AM) hydrogel.

[0022] Figure 3 This is the cyclic tensile stress-strain curve of the P(SBMA-AM)-Zn(TFSI)2 ion gel of Example 1 of the present invention.

[0023] Figure 4 The curve showing the change of the resistance value of the electrode according to Example 1 of the present invention with the number of bending times.

[0024] Figure 5 Schematic diagram of the geometry of the test platform of the highly sensitive bending sensor based on ionic polymer gel of the present invention.

[0025] Figure 6 The voltage output comparison of the highly sensitive bending sensors based on ionic polymer gel prepared in Examples 1-3 of the present invention at a bending angle of 90°.

[0026] Figure 7 This is the electrical signal output of the ionic flexible bending sensor prepared in Example 14 of the present invention when it is bent in the X and Y directions.

[0027] Figure 8 This is a schematic diagram of the structure of the ionic flexible bending sensor prepared in Example 14 of the present invention. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be further described below with reference to the accompanying drawings and through specific implementation methods. It should be understood that the embodiments are only used to illustrate the present invention and should not be regarded as specific limitations of the present invention.

[0029] The following combination Figure 1 The highly sensitive bending sensor based on ionic polymer gel described in the present invention (also known as ionic flexible bending sensor) is described.

[0030] The highly sensitive bending sensor based on ion polymer gel comprises an ion gel central sensitive layer (also referred to as an ion polymer layer) having a double network structure and an electrode layer attached in pairs to the surface of the ion gel central sensitive layer, wherein the number of pairs of electrodes is ≥1; preferably, the number of pairs of electrodes is ≥2; wherein the ion gel central sensitive layer is cross-linked and polymerized by monomers of zwitterionic polymers and monomers of flexible polymers to form a double network structure in which molecular chains are intertwined. Through the design of the double network structure, physical and chemical cross-linking is introduced into the ion gel central sensitive layer, and its mechanical properties are regulated to obtain an ion gel with small residual strain and good resilience, which can realize bending deformation with multiple degrees of freedom, has a long fatigue life, and is conducive to the repeated use stability of the device.

[0031] The structure of the ionic flexible sensor of the present invention includes a sandwich structure for realizing one degree of freedom direction recognition and a strip structure for realizing two degrees of freedom direction recognition.

[0032] In some technical solutions, the electrode layers are attached in pairs to the upper and lower surfaces of the strip-shaped ion gel central sensitive layer to form a sandwich structure sensor that realizes one degree of freedom direction recognition. In a specific embodiment, the electrode layers are attached to the upper and lower surfaces of the gel film to form a sandwich structure sensor.

[0033] In some technical solutions, the electrode layers are attached in pairs to the four side walls of the strip-shaped ion gel central sensitive layer to form a long strip structure sensor that realizes two-degree-of-freedom direction recognition.

[0034] The shape of the electrode layer includes but is not limited to a rectangle and a serpentine shape after topological optimization. In a preferred embodiment of the present invention, the electrode layer formed into a serpentine shape through topological optimization is attached to the four side walls of the strip-shaped ion gel central sensitive layer to form a long strip structure sensor that realizes bending recognition in two degrees of freedom directions. The serpentine electrode layer obtained through topological optimization is attached to the four walls of the strip-shaped ion gel central sensitive layer, which can more easily realize multi-dimensional deformation, including in-plane and out-of-plane bending.

[0035] The double network structure includes an elastic polymer skeleton formed by monomer polymerization of a flexible polymer and a polyzwitterionic channel formed by a zwitterionic polymer. The elastic polymer skeleton provides suitable mechanical strength and elasticity for the ionic polymer gel. The zwitterionic polymer forms a polyzwitterionic channel while regulating the mechanical properties of the gel, and improves the ion transport capacity of the material by means of electrostatic interaction. Specifically, the zwitterionic polymer carries a pair of cations and anions in its repeating unit (the cations and anions here refer to the zwitterionic groups of the zwitterionic polymer itself, and are different from the movable anions and cations provided by the free ion source), and exhibits equal charge stoichiometry and uniform charge distribution at the molecular level. The zwitterionic groups in the zwitterionic polymer interact with water molecules to form active centers, weaken the interaction between the migrating ions and the polymer chains, and reduce the resistance of the ions in the transmission. In addition, the zwitterionic groups provide migration channels respectively through electrostatic interactions, accelerate the transmission of electrolyte ions, and make the polyzwitterionic hydrogel have good electrical conductivity. At the same time, the anions and cations provided by the free ion source can move freely in the ion channel.

[0036] The ion gel central sensitive layer of the present invention has flexibility, good elasticity, adhesion and high ion conductivity. Flexibility enables the device to achieve deformation in multiple modes. Elasticity is a key indicator for the device to be reusable. The high adhesion strength between the ion gel central sensitive layer and the electrode layer is the key to achieving good and stable interface bonding of the device. High ion conductivity indicates that the ion gel central sensitive layer has good ion transport capacity, which is beneficial to improving the sensitivity of the sensor. In order to meet these conditions, the ion precursor solution of the ion gel central sensitive layer includes a free ion source and a solvent in addition to the monomers of the zwitterionic polymer and the monomers of the flexible polymer. In some technical schemes, the mass ratio of the monomers of the zwitterionic polymer, the monomers of the flexible polymer, the free ion source and the solvent is 1-2:3-6:0.5-20:5-40.

[0037] The monomer of zwitterionic polymer not only has high adhesion performance, but also can provide migration channels for ions. Due to the strong electrostatic repulsion between zwitterionic segments, the network structure will be loosened and the pores will be enlarged, which is more conducive to the transmission and migration of ions in the polymer network. The anionic and cationic groups in the zwitterionic polymer will interact with water molecules to form active centers, weaken the interaction between ions and polymer chains and between polymer chains, thereby accelerating ion migration and improving ionic conductivity. Preferably, the monomer of the zwitterionic polymer is methacrylic acid sulfobetaine.

[0038] The role of the monomer of the flexible polymer is to provide the gel with suitable mechanical strength and elasticity to meet the mechanical deformation requirements. Preferably, the monomer of the flexible polymer is acrylamide.

[0039] In a preferred embodiment, the mass ratio of acrylamide (AM) to sulfobetaine methacrylate (SBMA) is (3-5): 1. For example, when the mass ratio of acrylamide to sulfobetaine methacrylate in the ion gel used for the sensor is 3:1, it has the highest sensitivity.

[0040] The free ion source provides movable (migrating) anions and cations. Preferably, the cation size of the free ion source is smaller than the anion size. Selecting cations with smaller sizes and anions with larger sizes, so that the cations with smaller sizes move faster, can shorten the response time. Preferably, the anions and cations of the free ion source have a large difference in size. A large size difference can improve the response sensitivity of the device.

[0041] The free ion source can be selected from zinc trifluoromethylsulfonyl imide (Zn(TFSI)2), lithium trifluoromethylsulfonyl imide (Li(TFSI)), lithium chloride (LiCl) or other ion salts. The free ion source does not react with the polymer monomer of the central sensitive layer of the ion gel, nor with the material of the electrode layer.

[0042] The solvent is selected from at least one of water, an organic solvent and a deep eutectic solvent, and is preferably water.

[0043] In a preferred embodiment, the P(SBMA-AM) composite ion hydrogel containing Zn(TFSI)2 has the most excellent performance. The P(SBMA-AM) double network structure with good mechanical properties is formed in the gel system through physical and chemical crosslinking. Due to the presence of Zn(TFSI)2 ions providing ionic interactions, Zn 2+ Multivalent cations provide physical crosslinks to polymer chains, TFSI - The induced salting-out effect enhances the interaction between chains, and the hydrogel is toughened through the synergistic effect of ion-induced cross-linking and salting-out, which further enhances the mechanical properties of the gel, with minimal residual strain and good resilience, which is the key to the device's reusability. Due to the presence of zwitterionic groups in SBMA, the salt can be dissociated to produce charged ions. These charged anions and cations (as well as zwitterionic groups) have hydrogen bonding, electrostatic, ion dipole and other interaction forces with the substrate, so Zn(TFSI)2 provides more and stronger interactions, showing higher adhesion ability, resulting in the most stable and excellent interface bonding. The Zn(TFSI)2 ions in the gel system are better than other ions in the ability to transport and diffuse charges in the electrode material, which provides an answer to its superior sensing performance.

[0044] The electrode layer includes a flexible substrate and a conductive material coated on the surface of the flexible substrate.

[0045] In some technical solutions, the flexible substrate is selected from thermoplastic polyurethane (TPU) fiber membrane, polytetrafluoroethylene (PTFE) filter membrane, mixed cellulose (GSWP) filter membrane, polydimethylsiloxane (PDMS) film, silicone rubber (Ecoflex) film or other flexible organic polymer materials.

[0046] Preferably, the flexible substrate is selected from thermoplastic polyurethane (TPU) fiber membrane. It not only has good modulus matching with the ion gel, but also has low resistance (1.190Ω / cm). As an example, the thickness of the TPU fiber membrane is 10-200μm, and the diameter of the TPU fiber is 1-2μm. In a preferred embodiment of the present invention, the thickness of the TPU fiber membrane is 50μm, and the diameter of the TPU fiber is 1.5μm.

[0047] The conductive material includes, but is not limited to, a specific microstructured metal film, metal particles, carbon nanotubes, metal nanowires, graphene, MXene, conductive polymers or other low-dimensional conductive materials. In some technical solutions, the resistance of the conductive material is less than 100Ω / cm.

[0048] The conductive material is deposited on the surface of the flexible substrate to form a conductive layer. The conductive layer has high conductivity and flexibility. The thickness of the conductive layer can be changed as needed. For example, the thickness of the conductive layer is 100-500nm. In a preferred embodiment of the present invention, the thickness of the conductive layer is 200nm.

[0049] The electrode layer of the present invention has high conductivity, high elasticity, and conductivity stability under large strain. High conductivity is a prerequisite for the electrode to collect high-precision electrical signals, and high flexibility is the key to the electrode not being damaged under bending deformation. Compared with other combinations of flexible substrates and conductive materials, the electrode layer of the present invention has higher conductivity and flexibility. In a specific embodiment, the resistance of the electrode remains relatively stable after multiple cycles of bending, slightly increasing from the initial 1.190Ω / cm to 1.308Ω / cm after 10,000 cycles, and the resistance change rate is less than 10%.

[0050] The electrode layer selected in the present invention has high conductivity, flexibility, and ductility, and can be conformally attached to the central sensitive layer of the ion gel, adapt to the bending deformation of the gel material, and maintain conductivity stability during bending deformation. Such an electrode layer design is conducive to the device to obtain higher sensitivity, faster response speed and better device stability.

[0051] Figure 1This is a diagram of the sensing mechanism of the ionic flexible bending sensor. The sandwich-type sensor consists of two electrode layers and an ionic polymer layer. When the sensor is not bent, the ions are evenly distributed in the central sensitive layer of the ionic gel, and the potential difference on both sides of the central sensitive layer of the ionic gel is zero. When the sensor is bent, one side will stretch and expand, while the other side will be compressed. This will cause the ions to migrate from the compressed area to the expanded area, and due to the different sizes of anions and cations and different migration speeds, positive and negative potentials will accumulate on both sides of the sensor's electrodes. Therefore, this ionic sensor can not only generate electrical signals without an external power supply, but can also be used to distinguish different bending strain directions.

[0052] In terms of sensing principle, the present invention uses the potential difference formed by the asymmetric movement of cations and anions of the free ion source caused by bending to sense bending. The potential difference is closely related to the bending angle and amplitude, which provides feasibility for multi-degree-of-freedom sensing. In terms of device structure, the present invention uses ion gel as the central sensitive layer, on which multiple pairs of electrodes are deposited. The potential difference between each pair of electrodes is closely related to the bending angle and curvature. By analyzing the signal differences between multiple pairs of electrodes, the bending direction and amplitude can be quickly identified. This solves the problem that existing bending sensors are difficult to distinguish bending angles.

[0053] The ion gel central sensitive layer used in the ion sensor of the present invention has good mechanical properties and high ion conductivity. The ion gel central sensitive layer is a polymer material with high viscosity, which can fit tightly with the electrode material, which is conducive to achieving good and stable interface bonding, thereby improving the sensing performance. Not only that, the electrode layer of the ion sensor of the present invention has a low modulus, which can be well conformal with the highly flexible ion polymer material, which is conducive to reducing the contact impedance of the electrode layer and the ion polymer layer, achieving high-quality electrical signal transmission, and also realizing multi-degree-of-freedom bending and tensile strain detection. The sensor prepared based on the excellent material design described above has ultra-high sensitivity, good stability, wide detection range and small detection limit, and can achieve high-frequency response and identify different bending directions.

[0054] In particular, the double network gel involved in the present invention comprises an elastic polymer skeleton formed by polymerization of flexible polymer monomers and a polyzwitterionic channel formed by a zwitterionic polymer. The elastic polymer skeleton provides the ionic polymer gel with suitable mechanical strength and elasticity, so that it can meet the mechanical deformation requirements. The zwitterionic polymer forms a polyzwitterionic channel while regulating the mechanical properties of the gel, and improves the ion transport capacity of the material with the help of active centers. In addition, the introduction of zwitterions also gives the gel excellent adhesion, and the interface adhesion ability is improved by generating multiple interactions between the abundant ionic groups and anions and cations in the gel and the material surface.

[0055] The following is an exemplary description of the method for preparing the highly sensitive bending sensor based on ionic polymer gel according to the present invention.

[0056] Prepare the electrode layer. The preparation method of the electrode layer includes but is not limited to the filtration method, the spraying method, and the vacuum evaporation method.

[0057] For example, the electrode layer is prepared by vacuum evaporation of metal particles on the TPU fiber membrane. The vacuum evaporation method allows the metal nanoparticles to be uniformly deposited on the TPU fiber membrane, and the resistance and thickness of the prepared flexible conductive layer are relatively uniform. In a preferred embodiment, silver particles are selected and vacuum evaporation is used to form a silver nanoparticle layer on the TPU fiber membrane. The amount of silver particles used is, for example, 1.5-4.5 mg / cm 2 .

[0058] As an example, 5 g of thermoplastic polyurethane (TPU) is first dissolved in 20 g of N,N-dimethylformamide (DMF) to prepare a spinning solution with a mass fraction of 20%, and a TPU fiber membrane is prepared by electrospinning. Then, the metallic silver material is uniformly deposited on the TPU polymer flexible substrate by evaporation. In a specific embodiment, the thickness of the flexible substrate layer is 50 μm, and the thickness of the conductive layer is 200 nm.

[0059] Prepare an ion gel center sensitive layer. The preparation method of the ion gel center sensitive layer is a one-pot method. After the monomers of the flexible polymer and the monomers of the zwitterionic polymer are uniformly mixed with the solvent, a free ion source is added and stirred for a period of time; then an initiator is added and stirred for a period of time to obtain a solution; after the solution is uniformly mixed, it is injected into a mold for curing; after cooling, it is taken out and demolded, and cut into an ion gel center sensitive layer. Curing conditions include but are not limited to thermal curing and light curing. In a preferred embodiment, thermal curing is used. The initiator is preferably potassium persulfate (KPS). The curing time can be 9 hours.

[0060] There is no particular order in which the electrode layer is prepared and the ion gel central sensitive layer is prepared.

[0061] The electrode layer is attached to the surface of the central sensitive layer of the ion gel to prepare a highly sensitive bending sensor based on the ion polymer gel.

[0062] In some technical solutions, a conductive tape is arranged on part of the surface of the conductive layer, and a conductive silver paste is coated and filled to extend the gap between the conductive layer and the conductive tape and to make a conductive connection, so as to generate effective electrical signal transmission between the electrode layer and the external circuit.

[0063] The device is packaged and applied to sensing monitoring. The material of the packaging layer can be selected from polyethylene terephthalate, polyimide, polydimethylsiloxane, polymethyl methacrylate or silicone rubber. The packaging layer has flexibility, ductility and solvent barrier properties. Silicone rubber is preferred.

[0064] In summary, the sensor of the present invention is a flexible bending sensor with high sensitivity and capable of realizing multi-degree-of-freedom bending detection. The ionic flexible bending sensor of the present invention has good and stable interface bonding: on the one hand, the zwitterionic groups in the central sensitive layer of the ion gel will generate hydrogen bonding, electrostatic, ion dipole and other interaction forces with the electrode layer, showing high adhesion ability and can firmly adhere to the surface of the electrode layer; on the other hand, the low modulus electrode material has a good modulus match with the ionic polymer material and is not easy to fall off during the bending process. Stable interface bonding is conducive to the device to obtain higher sensitivity, faster response speed and better device stability. Moreover, the preparation method of the sensor of the present invention is simple to operate and low in cost. It has the potential to be widely used in human activity monitoring (such as upward and downward bending, inward and outward rotation of the wrist) and human-computer interaction fields, realizing multi-degree-of-freedom bending recognition, and has very important research value.

[0065] In the present invention, the influence of the addition of free ion source and zwitterionic polymer on the sensitivity of sensor is studied. The first is the difference in the size of anions and cations of the free ion source. The smaller the radius of cations, the faster the migration speed. Since anions have a larger radius, the migration speed is slower than that of cations. Therefore, the greater the difference in the size of anions and cations, the greater the potential difference can be formed on both sides of the electrode, thereby improving the sensitivity of the device. The second is the charge number of the ion. The greater the charge number, the higher the potential difference output, and the higher the sensitivity. Finally, the adhesion of the gel after adding zwitterionic polymer monomers is mainly to utilize the hydrogen bonds, electrostatic forces, ion-dipole, and cation-π bond interactions generated by the abundant ionic groups and anions and cations in the gel and the surface of the material, thereby enhancing the adhesion strength, improving the interface bonding, enhancing the ion interaction effect, obtaining a stronger signal, and realizing highly sensitive detection.

[0066] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0067] Example 1

[0068] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0069] (1) Preparation of ionic polymer layer: 1.5 g of acrylamide (AM), 0.5 g of sulfobetaine methacrylate (SBMA) and 10 mL of deionized water were uniformly mixed, and 6.26 g of Zn(TFSI)2 was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 9 h; after cooling, it was removed from the mold and cut into 40 × 15 × 2 mm ionic polymer strips.

[0070] (2) Preparation of electrode layer: 5 g of thermoplastic polyurethane (TPU) was dissolved in 20 g of N,N-dimethylformamide (DMF) to prepare a spinning solution with a mass fraction of 20%, and a TPU fiber membrane was prepared as a polymer flexible substrate by an electrospinning method; then, 0.45 g of metallic silver particle material was uniformly deposited on a 10×10 cm TPU polymer flexible substrate by vacuum evaporation to obtain a TPU / Ag electrode material; the electrode material was cut into a 80×10 mm rectangle, a 5 mm wide copper-nickel conductive tape was set on part of the surface of the conductive layer, and a conductive silver paste was coated to fill the pores to prepare an electrode layer.

[0071] (3) Assembly: The electrode layers are attached to the upper and lower surfaces of the ionic polymer layer, respectively, to prepare an ionic bending sensor with a sandwich structure.

[0072] (4) Packaging: Finally, the device is packaged with silicone rubber and applied to sensor monitoring.

[0073] Figure 3 The cyclic tensile stress-strain curve of P(SBMA-AM)-Zn(TFSI)2 ion gel is shown. By constructing a double network structure, physical and chemical crosslinking are introduced into the hydrogel. The formation of covalent bonds in the chemical crosslinking can provide the gel with suitable mechanical properties. The generation of intermolecular hydrogen bonds, electrostatic forces, and ion dipole effects in the physical crosslinking can achieve energy dissipation, reduce residual strain, and form a gel with good soft elasticity. According to the experimental results, the ion gel with the addition of Zn(TFSI)2 showed extremely small residual strain (0.92%), indicating that the gel has very good elasticity as an ionic polymer matrix, which meets the requirements of the sensor being able to be reused.

[0074] Sensitivity is one of the main performance parameters of flexible strain sensors and is crucial for the application of sensors. The strain factor (sensitivity, S) can be defined as: S = ΔV × ε -1 , where ΔV is the change in voltage under strain, ΔV = V-V0, and ε is the strain of the sensor.

[0075] Figure 5 The geometrical schematic diagram of the test platform of the long-range stable ionic flexible bending sensor prepared in Example 1 is shown. A model is established using the Euler-Bernoulli theory to calculate the strain under the corresponding displacement.

[0076] The sensor was fixed on a PET film with an initial free length of 5 cm. The two ends of the PET film were then fixed between an electric translation stage, and a computer-controlled stepper motor was used to control the displacement and speed of the film. The tensile bending strain was calculated using the software MATLAB based on the Euler-Bernoulli theory, and the two sides of the electrode were connected to an electrochemical station to test the change in open circuit voltage at the upper and lower ends of the electrode during the bending process.

[0077] The thickness of the film sensor is h and the length is L. When the displacement platform moves x, the film bends. Assuming the central angle of the arc is θ, the radius is R. Based on the geometric relationship, the equation is listed:

[0078] θ×R=L

[0079]

[0080] Knowing L and x, we can get θ and R from the equation.

[0081] In the present invention, the bending angle is 180°-θ. Finally, the bending strain is calculated using the Euler-Bernoulli approximation theory to obtain the strain corresponding to the displacement.

[0082]

[0083] Example 2

[0084] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0085] (1) Preparation of ionic polymer layer: 1.5 g of acrylamide (AM), 0.5 g of sulfobetaine methacrylate (SBMA) and 10 mL of deionized water were uniformly mixed, and then 2.87 g of Li(TFSI) was added and stirred for 0.5 h. Then, 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution. After the solution was uniformly mixed, it was ultrasonicated at 20-30°C for 3 min. Finally, it was injected into a homemade mold and thermally cured for 9 h. After cooling, it was removed from the mold and cut into 40×15×2 mm ionic polymer strips.

[0086] Steps (2)-(4) are as in Example 1.

[0087] Example 3

[0088] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0089] (1) Preparation of ionic polymer layer: 1.5 g of acrylamide (AM), 0.5 g of sulfobetaine methacrylate (SBMA) and 10 mL of deionized water were uniformly mixed, and 0.42 g of LiCl was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 9 h; after cooling, it was removed from the mold and cut into 40 × 15 × 2 mm ionic polymer strips.

[0090] Steps (2)-(4) are as in Example 1.

[0091] The adhesion performance test method is as follows: the adhesion strength is measured by a pressure gauge (M5-20, Mark-10, America). A compressive prestress of 20N is first applied between the electrode material and the gel. After 20s, the pressure gauge is separated at a moving rate of 50mm / min. The tensile adhesion strength is determined by the following formula:

[0092]

[0093] Where F is the peak force (tension is a negative value) read by the dynamometer during the movement, indicating the moment when the gel film and the electrode film separate. S is the contact area between the electrode and the gel film, which is a circle with a diameter of 1.2 cm.

[0094] The adhesion strengths of the ionomer layer and the electrode layer prepared in Examples 1-3 were 24.1 kPa, 22.9 kPa, and 20.3 kPa, respectively. Among them, the P(SBMA-AM) ion gel containing Zn(TFSI)2 prepared in Example 1 showed the strongest adhesion, and thus had the tightest combination with the electrode material, and accordingly, the most superior sensing performance.

[0095] Figure 4 The curve of the resistance change of the electrode of Example 1 under bending cycle is shown. The electrode material not only maintains good stability in the bent state, but also has fatigue resistance and a long service life. It remains relatively stable after multiple cycles of bending. The resistance of the electrode slightly increases from the initial 1.190Ω / cm to 1.308Ω / cm after 10,000 cycles. The electrode still has high conductivity under multiple bending strains. The specific reason is analyzed as follows: the flexible substrate TPU substrate in the electrode layer has good flexibility and fiber network structure, and can still maintain the conductive path without breaking after multiple bending.

[0096] Figure 6 The voltage output changes of the highly sensitive bending sensors based on ion polymer gel prepared in Examples 1-3 at a bending angle of 90° are demonstrated. Among them, the sensor using the P(SBMA-AM) ion gel containing Zn(TFSI)2 in Example 1 showed the highest voltage output value of 395mV; the voltage output value of the sensor using the P(SBMA-AM) ion gel containing LiCl in Example 3 was 210mV; the voltage output value of the sensor using the P(SBMA-AM) ion gel containing Li(TFSI) in Example 2 was 173mV. The calculation formula of sensitivity is: S = ΔV × ε -1 , where ΔV is the change in voltage under strain, ΔV=V-V0, and ε is the strain of the sensor. Therefore, the sensor of Example 1 using P(SBMA-AM) ion gel containing Zn(TFSI)2 has the highest sensitivity (126mV / 1% strain).

[0097] Example 4

[0098] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0099] (2) Preparation of electrode layer: 5 g of thermoplastic polyurethane (TPU) was dissolved in 20 g of N,N-dimethylformamide (DMF) to prepare a spinning solution with a mass fraction of 20%, and a TPU fiber membrane was prepared as a polymer flexible substrate by an electrospinning method; then, 1 mg of carbon nanotubes was uniformly deposited on a TPU polymer flexible substrate with a diameter of 5 cm by suction filtration to obtain a TPU / carbon nanotube electrode material; the electrode material was cut into a 50×10 mm rectangle, a 5 mm wide copper-nickel conductive tape was set on part of the surface of the conductive layer, and a conductive silver paste was coated to fill the gaps to prepare an electrode layer.

[0100] Steps (1), (3) and (4) are as in Example 1.

[0101] Example 5

[0102] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0103] (2) Preparation of electrode layer: 1 mL of silver nanowire solution (concentration 1 mg / mL) was dispersed in 20 mL of alcohol to obtain a silver nanowire dispersion; the silver nanowire (AgNWs) dispersion was then evenly sprayed onto a 10×10 cm clean aluminum foil using a spray gun. During the spraying process, the aluminum foil was placed on a heating table at 80°C; the aluminum foil with AgNWs loaded on the surface was cut into 60×10 mm rectangular electrode strips to prepare the electrode layer.

[0104] (3) Assembly: The ionic polymer film is stretched to 60×20×2 mm, and the surface of the electrode rectangular strip with the silver nanowires is attached to the ionic polymer film; then the aluminum foil is gently torn off to allow the silver nanowires to be completely transferred to the ionic polymer film; a 5 mm wide copper-nickel conductive tape is placed on part of the surface of the conductive layer, and a conductive silver paste is applied to fill the gaps to prepare an ionic bending sensor.

[0105] Steps (1) and (4) are as in Example 1.

[0106] Example 6

[0107] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0108] (2) Preparation of electrode layer: Take Ti3C2T with a concentration of 2.26 mg / mL x 221 μL of / AgNPs (10 wt%) solution was dispersed in 20 mL of alcohol to obtain a dispersion; GSWP was then used as a filter membrane and a flexible substrate to filter the Ti3C2T x / AgNPs are uniformly deposited on the surface of the filter membrane; the surface is loaded with Ti3C2Tx The flexible substrate of / AgNPs was cut into 50×10 mm electrode rectangular strips, a 5 mm wide copper-nickel conductive tape was set on part of the surface of the conductive layer, and conductive silver paste was coated to fill the gaps to prepare an electrode layer.

[0109] Steps (1), (3) and (4) are as in Example 1.

[0110] Example 7

[0111] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0112] (2) Preparation of electrode layer: 1 mL of silver nanowire solution (concentration 1 mg / mL) was dispersed in 20 mL of alcohol to obtain a silver nanowire dispersion; PTFE was then used as a filter membrane to uniformly deposit AgNWs on the surface of the filter membrane by suction filtration; the filter membrane loaded with AgNWs on the surface was cut into 50×10 mm rectangular electrode strips; a PDMS film was prepared and taken out when it was in a semi-cured state, and the filter membrane with AgNWs was attached to the PDMS surface for prepolymerization and continued thermal curing; after taking out, the filter membrane was gently torn off and cut into 50×10 mm AgNWs electrode films with a flexible substrate PDMS, a 5 mm wide copper-nickel conductive tape was set on part of the surface of the conductive layer, and a conductive silver paste was applied to fill the gaps to prepare an electrode layer.

[0113] Steps (1), (3) and (4) are as in Example 1.

[0114] Example 8

[0115] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0116] (2) Preparation of electrode layer: 5 g of thermoplastic polyurethane (TPU) was dissolved in 20 g of N,N-dimethylformamide (DMF) to prepare a spinning solution with a mass fraction of 20%, and a TPU fiber membrane was prepared as a flexible substrate by an electrospinning method; then, 0.3 g of metallic silver particle material was uniformly deposited on a 10×10 cm TPU polymer flexible substrate by vacuum evaporation; the electrode material was cut into a 80×10 mm rectangle, a 5 mm wide copper-nickel conductive tape was set on part of the surface of the conductive layer, and a conductive silver paste was applied to fill the gaps to prepare an electrode layer.

[0117] Steps (1), (3) and (4) are as in Example 1.

[0118] Example 9

[0119] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0120] (1) Preparation of ionic polymer layer: 1.5 g of acrylamide (AM), 0.5 g of sulfobetaine methacrylate (SBMA) and 10 mL of deionized water were uniformly mixed, and then 3.13 g of Zn(TFSI)2 was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 9 h; after cooling, it was removed from the mold and cut into 40 × 15 × 2 mm ionic polymer strips.

[0121] Steps (2)-(4) are as in Example 1.

[0122] Example 10

[0123] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0124] (1) Preparation of ionic polymer layer: After 1.5 g of acrylamide (AM) was uniformly mixed with 10 mL of deionized water, 6.26 g of Zn(TFSI)2 was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 9 h; after cooling, it was removed from the mold and cut into 40 × 15 × 2 mm ionic polymer strips.

[0125] Steps (2)-(4) are as in Example 1.

[0126] Figure 2 Scanning electron microscope micrographs of single cross-linked PAM hydrogel and multi-cross-linked P(SBMA-AM) hydrogel are shown. Both PAM and P(SBMA-AM) hydrogels have honeycomb porous structures, and the pore size distribution of the two is 40-65μm and 55-130μm, respectively. The reasons for the difference in pore size are analyzed: SBMA is a zwitterion, in which the quaternary ammonium group and the sulfonic acid group carry a pair of opposite charges. The molecular chain formed by the copolymerization of SBMA and AM will increase the concentration of anions and cations, resulting in an enhanced interaction between the hydrogel and water molecules, making it easier for water molecules to enter the hydrogel network, resulting in a loose network structure inside the hydrogel. In addition, due to the strong electrostatic repulsion between the zwitterionic segments, it is also the reason for the loose network. Therefore, the multi-cross-linked P(SBMA-AM) hydrogel with a larger pore size is more conducive to the transmission and migration of ions in the polymer network.

[0127] The mechanical properties, mechanical adhesion properties, and electrical properties of the ionic polymer material in Example 10 are all reduced compared to those in Example 1, and the sensitivity of the device made therefrom is also low. Among them, the residual strain of the ionic gel in Example 10 is 3.73%, the adhesion strength with the electrode material is 13 kPa, the ionic conductivity is 12.6 ms / cm, and the sensitivity of the corresponding device is 32 mV / 1% strain.

[0128] Embodiment 11

[0129] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0130] (1) Preparation of ionic polymer layer: 1.6 g of acrylamide (AM), 0.4 g of sulfobetaine methacrylate (SBMA) and 10 mL of deionized water were uniformly mixed, and 6.26 g of Zn(TFSI)2 was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 9 h; after cooling, it was removed from the mold and cut into 40 × 15 × 2 mm ionic polymer strips.

[0131] Steps (2)-(4) are as in Example 1.

[0132] Example 12

[0133] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0134] (1) Preparation of ionic polymer layer: 1.5 g of acrylamide (AM), 0.5 g of sulfobetaine methacrylate (SBMA) and 10 mL of ethanol were uniformly mixed, and 6.26 g of Zn(TFSI)2 was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 9 h; after cooling, it was removed from the mold and cut into 40 × 15 × 2 mm ionic polymer strips.

[0135] Steps (2)-(4) are as in Example 1.

[0136] Embodiment 13

[0137] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0138] Steps (1) to (3) refer to Example 1, without encapsulation. In the present invention, the weight of the ionic hydrogel containing Zn(TFSI)2 decreases to 55.6% after 12 hours when it is not encapsulated; after encapsulation, the weight can be maintained at 95.6% after 12 hours. Therefore, the encapsulated gel can prevent the volatilization of water, so that the sensor can be used in long-term monitoring, further improving the stability and service life of the device.

[0139] Embodiment 14

[0140] The highly sensitive bending sensor based on ionic polymer gel according to the present invention is prepared according to the following process steps:

[0141] (1) Preparation of ionic polymer layer: 1.5 g of acrylamide (AM), 0.5 g of sulfobetaine methacrylate (SBMA) and 10 mL of deionized water were uniformly mixed, and 6.26 g of Zn(TFSI)2 was added and stirred for 0.5 h; then 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 h to obtain a transparent solution; after the solution was uniformly mixed, it was ultrasonicated at 20-30 °C for 3 min; finally, it was injected into a homemade mold and thermally cured for 12 h; after cooling, it was removed from the mold and cut into 40×5×5 mm ionic polymer strips.

[0142] (2) Preparation of electrode layer: 5 g of thermoplastic polyurethane (TPU) was dissolved in 20 g of N,N-dimethylformamide (DMF) to prepare a spinning solution with a mass fraction of 20%, and a TPU fiber membrane was prepared as a polymer flexible substrate by an electrospinning method; then, 0.45 g of metallic silver particle material was uniformly deposited on a 10×10 cm TPU polymer flexible substrate by vacuum evaporation to obtain a TPU / Ag electrode material; the electrode material was cut into a 80×5 mm rectangle, and then topologically optimized to form a serpentine electrode structure to facilitate better deformation; and a 5 mm wide copper-nickel conductive tape was set on part of the surface of the conductive layer, and a conductive silver paste was applied to fill the gaps.

[0143] (3) Assembly: The electrode layer is attached to the four side walls of the ionic polymer layer to prepare a strip-shaped ionic bending sensor.

[0144] (4) Packaging: Finally, the device is packaged with silicone rubber and applied to sensor monitoring.

[0145] Figure 7The electrical signal output of the ionic flexible bending sensor prepared in Example 14 when bending in the X and Y directions is shown. The Z-axis direction is the length direction of the ion gel central sensitive layer, the Y-axis direction is the thickness direction of the ion gel central sensitive layer, and the X-axis direction is the width direction of the ion gel central sensitive layer. Wherein X represents the voltage output of the X-axis electrode pair, Y+ represents the voltage output of the Y-axis electrode pair when bending in the positive direction of the Y axis, and Y- represents the voltage output of the Y-axis electrode pair when bending in the negative direction of the Y axis. When bending 90° in the positive direction of the Y axis, the stretching and compression on both sides of the Y-axis electrode cause the migration of anions and cations in the Y direction, and accumulate on both sides of the Y direction respectively. As the bending angle increases, the voltage value collected in the Y direction gradually increases, forming an upward peak; and the deformation generated in the Y direction has almost no effect on the X direction, so the voltage value collected in the X direction has almost no obvious change. Similarly, when bending 90° in the negative direction of the Y axis, anions and cations migrate to different electrode sides, so the voltage value collected gradually decreases with the increase of the bending angle, forming a downward peak; there is still no obvious change in the X direction. Similarly, when bending in the positive and negative directions of the X-axis, similar signal peaks are generated: the X-axis electrode pair generates upward and downward peaks when bending in the positive and negative directions of the X-axis, while the voltage output by the Y-axis electrode pair has basically no obvious change. This result shows that the sensor has the function of dual-degree-of-freedom bending recognition.

[0146] Comparative Example 1

[0147] The ionic polymer gel was prepared according to the following process steps:

[0148] After 0.5 g of sulfobetaine methacrylate (SBMA) was evenly mixed with 10 mL of deionized water, 4 mg of N,N'-methylenebisacrylamide (MBAA) and 20 mg of potassium persulfate (KPS) were added and stirred for 1 hour to obtain a transparent solution; after the solution was evenly mixed, it was ultrasonicated at 20-30°C for 3 minutes; finally, it was injected into a homemade mold and thermally cured for 9 hours.

[0149] Pure polymethacrylate sulfobetaine network has poor mechanical properties, and the gel is too soft to be molded, so it cannot be used as an ionic polymer material for devices.

Claims

1. A highly sensitive bending sensor based on ionic polymer gel, characterized in that: The highly sensitive bending sensor based on ionic polymer gel comprises an ionic gel central sensitive layer with a double network structure and electrode layers attached in pairs to the surface of the ionic gel central sensitive layer, wherein the number of pairs of electrodes is ≥1; preferably, the number of pairs of electrodes is ≥2; wherein the ionic gel central sensitive layer is cross-linked and polymerized by monomers of zwitterionic polymers and monomers of flexible polymers to form a double network structure in which molecular chains are intertwined with each other.

2. The highly sensitive bending sensor based on ionic polymer gel according to claim 1, characterized in that: The electrode layers are attached in pairs to the upper surface and the lower surface of the strip-shaped ion gel central sensitive layer to form a sandwich structure sensor that realizes one degree of freedom direction recognition.

3. The highly sensitive bending sensor based on ionic polymer gel according to claim 1, characterized in that: The electrode layers are attached in pairs to the four side walls of the strip-shaped ion gel central sensitive layer to form a long strip structure sensor that can realize two-degree-of-freedom direction recognition.

4. The highly sensitive bending sensor based on ionic polymer gel according to claim 2 or 3, characterized in that: The electrode layer is rectangular or serpentine-shaped by topological optimization; preferably, the electrode layer formed into a serpentine shape by topological optimization is attached in pairs to the four side walls of the strip-shaped ion gel central sensitive layer to form a long strip structure sensor that realizes bending recognition in two degrees of freedom directions.

5. The highly sensitive bending sensor based on ionic polymer gel according to any one of claims 1 to 4, characterized in that: The double network structure includes an elastic polymer skeleton formed by polymerization of monomers of a flexible polymer and a polyzwitterionic channel formed by a zwitterionic polymer; preferably, the monomer of the zwitterionic polymer is methacrylic acid sulfobetaine, and the monomer of the flexible polymer is acrylamide.

6. The highly sensitive bending sensor based on ionic polymer gel according to any one of claims 1 to 5, characterized in that: The ion precursor solution of the central sensitive layer of the ion gel includes, in addition to monomers of zwitterionic polymers and monomers of flexible polymers, a free ion source and a solvent; wherein the anions and cations of the free ion source can move freely in the polyzwitterionic channel; preferably, the cations of the free ion source are smaller in size than the anions; more preferably, the size difference between the anions and cations of the free ion source is between 0.1-0.8 nm.

7. The highly sensitive bending sensor based on ionic polymer gel according to claim 6, characterized in that: The free ion source is selected from one or more of zinc trifluoromethylsulfonyl imide, lithium trifluoromethylsulfonyl imide, and lithium chloride; the solvent is selected from at least one of water, an organic solvent, and a deep eutectic solvent, preferably water.

8. The highly sensitive bending sensor based on ionic polymer gel according to any one of claims 1 to 7, characterized in that: The electrode layer includes a flexible substrate and a conductive material coated on the surface of the flexible substrate; the conductive material is selected from one or more of a specific microstructured metal film, metal particles, carbon nanotubes, metal nanowires, graphene, MXene, and a conductive polymer; preferably, the conductive material is deposited on the surface of the flexible substrate to obtain the electrode layer.

9. The highly sensitive bending sensor based on ionic polymer gel according to any one of claims 1 to 8, characterized in that: The highly sensitive bending sensor based on ionic polymer gel senses bending through the potential difference formed by the asymmetric movement of anions and cations in a free ion source caused by bending.

10. The highly sensitive bending sensor based on ionic polymer gel according to any one of claims 1 to 9, characterized in that: The preparation method comprises: shaping and curing an ion precursor solution of an ion gel central sensitive layer to obtain an ion gel central sensitive layer; attaching electrode layers in pairs to the surface of the ion gel central sensitive layer to obtain the highly sensitive bending sensor based on the ion polymer gel.

Citation Information

Patent Citations

  • pH and oxidation-reduction dual-sensitive layer cross-linking nanoparticle as well as preparation method and application thereof

    CN104231193A

  • Transparent and flexible photoelectric sensor and preparation method thereof

    CN105633283A

  • Non-woven composite material, structural strain sensor, distributed monitoring system and method

    CN110906858A

  • Flexible bending sensor and manufacturing method thereof

    CN111059999A

  • Transparent flexible sensor and preparation method thereof, electronic skin and wearable device

    CN111297321A

Cited By

  • Bicontinuous phase ionic piezoelectric hydrogel, sensor and preparation method thereof

    CN122628524A